Perancangan Sistem Informasi Ketersediaan Darah Guna Menunjang Tata Kelola Rekam Medis Elektronik dengan Menerapkan Metode Agile - Isya, Ghen Maulana; Syahidin, Yuda; Sari, Irda; Sukmawijaya, Jeri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Electronic medical records are recommended to be implemented in every hospital to facilitate fast data collection and the accuracy of the processed data is correct, but manual data collection still occurs in computerized systems such as entering data into Microsoft excel. The weaknesses in manual medical record data collection are quite a lot even though security is maintained by using a computer such as the length of time for data collection and tends to be incomplete data. The purpose of this research is a practical system in software that can facilitate medical record data collection because manual data entry occurs in the blood availability system at Limijati Mother and Child Hospital. The Agile method is used in this research as a method that involves users into the process of designing information systems that can be tailored to user needs without requiring a long time. Not only the system development method, the black box testing method is used as an application function test. The software used is Microsoft Visual Studio 2012 and Microsoft Access 2016 database. It is hoped that the resulting information system on blood availability can help easy data collection without any erroneous data so that data can be accepted.